Physics of Internal Photoemission and Its Infrared Applications in the Low-Energy Limit. (28th January 2016) - Lao, Y. F.; Perera, A. G. U.
Abstract : Internal photoemission (IP) correlates with processes in which carriers are photoexcited and transferred from one material to another. This characteristic allows characterizing the properties of the heterostructure, for example, the band parameters of a material and the interface between two materials. IP also involves the generation and collection of photocarriers, which leads to applications in the photodetectors. This review discusses the generic IP processes based on heterojunction structures, characterizingp -type band structure and the band offset at the heterointerface, and infrared photodetection including a novel concept of photoresponse extension based on an energy transfer mechanism between hot and cold carriers.